Answer:
Explanation:
Let's start by evaluating a² − b² and a² + b².
a² − b²
= (cos α + cos β)² − (sin α + sin β)²
= cos² α + 2 cos α cos β + cos² β − (sin² α + 2 sin α sin β + sin² β)
= (cos² α − sin² α) + (cos² β − sin² β) + 2 (cos α cos β − sin α sin β)
= cos (2α) + cos (2β) + 2 cos (α + β)
a² + b²
= (cos α + cos β)² + (sin α + sin β)²
= cos² α + 2 cos α cos β + cos² β + sin² α + 2 sin α sin β + sin² β
= 2 + 2 (cos α cos β + sin α sin β)
= 2 + 2 cos (α − β)
cos (α + β)
Multiply top and bottom by 2 + 2 cos (α − β).
= cos (α + β) (2 + 2 cos (α − β)) / (2 + 2 cos (α − β))
= (2 cos (α + β) + 2 cos (α − β) cos (α + β)) / (2 + 2 cos (α − β))
Product to sum:
= (2 cos (α + β) + cos (α + β − (α − β)) + cos(α + β + α − β)) / (2 + 2 cos (α − β))
= (2 cos (α + β) + cos (2β) + cos (2α)) / (2 + 2 cos (α − β))
Substitute:
= (a² − b²) / (a² + b²)
atan(1/x) − atan(2 − x) = π/12
Angle difference formula:
atan((1/x − (2 − x)) / (1 + (1/x)(2 − x))) = π/12
atan((1/x − 2 + x) / (1 + 2/x − 1)) = π/12
atan((1/x − 2 + x) / (2/x)) = π/12
atan((1 − 2x + x²) / 2) = π/12
Take tangent of both sides.
(1 − 2x + x²) / 2 = tan(π/12)
1 − 2x + x² = 2 tan(π/12)
Half angle formula:
1 − 2x + x² = 2 sin(π/6) / (1 + cos(π/6))
1 − 2x + x² = 1 / (1 + √3 / 2)
1 − 2x + x² = 2 / (2 + √3)
Rationalize:
1 − 2x + x² = 2 (2 − √3) / (4 − 3)
1 − 2x + x² = 2 (2 − √3)
1 − 2x + x² = 4 − 2√3
Factor and solve:
(x − 1)² = 4 − 2√3
x − 1 = ±√(4 − 2√3)
x = 1 ± √(4 − 2√3)